KKN TEMATIK- PEMBERDAYAAN MASYARAKAT ERA PANDEMI COVID-19 DESA KARANGNONGKO KABUPATEN KLATEN - Sri Nugroho, Arif Julianto (Jurnal Abadimas Adi Buana, 2022)
The activity of KKNT-PPM in covid-19 pandemic era in Karangnongko Village, Klaten Regency aims to improve the management system of the tourism village in the pandemic era. This is an effort to increase the communities participation in family economic development, The models which is done include 1) Entrepreneurship Capacity Building and 2) Technology and Literacy Knowledge Transfer. To achieve the goals, several activity plans are proposed in the implementation of the KKNT-PPM Program in Karangnongko Village as follows. a) Establishment of a Tourism Village Management Institution, b) Formation a new marketing network in Tourism Village (distribution channel) in the covid-19 pandemic era, c) Training and developing the local crafts, and d) Learning model for elementary school students in pandemic era. From those activities, there is a positive result which is obtained where the society, learners, were enthusiastic in joining program and it is led to the formation of a foundation for empowering tourism village and entrepreneurship in the new normal after covid-19 pandemic